DAMPAK PRIVACY TERHADAP E-VENDOR TRUST KONSUMEN DI SISTEM E-COMMERCE - Probohudono, Agung Nur (Universitas Slamet Riyadi, 2009)
ABSTRACT The Information system base on the internet of many used by moment of internet represent the open platform (open platform) so that eliminate the company of at certain vendor like if using closed system (proprietary systems). Internet represents the most economic media to be used as information system bases. Electronic Commerce represent the usage of computer network to conduct the purchasing and goods sale, service and information electronically Besides level of benefit capable to the through the network which world, internet represent the system of computer network owning susceptance (vulnerable). Long distance dissociating consumer and situs expense and infrastructure of internet yield the uncertainty in transacting by e-vendor so that customer client have the risk of loss of money and privacy. Trust become the catalyst to transaction of seller and buyer making consumer have the big expectation to satisfy to the relation link. Trust to electronic vendor determine the consumer decision to do conduct the relation of business of e-commerce. The vendor will hinder the consumer use the product of web vendor. Key element from privacy is operation of related to accessing physical to of their his self and requirement independent of related to identity and relation of interpersonal Web site privacy influence the trust consumer, influencing attitude and desire buy from consumer. Keywords: privacy, trust, e-commerce